Initial public perceptions of carbon geosequestration: implications for engagement and environmental risk communication strategies. (22nd February 2008) - Miller, E.; Summerville, J.; Buys, L.; Bell, L.
Despite active scientific research into the geological sequestration of carbon dioxide, little is known about how the public perceives geosequestration technologies designed to reduce greenhouse gas emissions by capturing and storing carbon dioxide in underground sites. Thus, through an online survey (n = 1273), this study investigated Australians' knowledge and perceptions of carbon geosequestration. Most respondents believed that it was important for Australia to reduce carbon dioxide emissions, yet only 18% had previously heard of geosequestration and only 5% closely followed the greenhouse debate. People were keen to participate in public discussions and learn more before forming a definite opinion, although many had 'Not-In-My-Backyard' reactions and raised concerns about the risks and effectiveness of technology and the trustworthiness of organisations. By highlighting current perceptions and knowledge about geosequestration, this research informs environmental risk communication strategies and emphasises the importance of early engagement, education and partnerships between stakeholders for fostering informed decision-making about its use in the Australian context.